Interactive projection mapping installation - Ng, Ye Dong (Nanyang Technological University, 2021)
The motivation of this Final Year Project (FYP) was to ultimately achieve an installation display piece, suitable for the use of audience interaction during events organised by the faculty and/or the university. The need for such an installation was derived from a desire to showcase the inter-disciplinary aspects of Information Engineering and Media (IEM) and to portray these aspects visually to its audience. In order to communicate the technicalities of IEM, this FYP aims to explore the possibilities of interactive installations while designing and constructing physical structures, software and hardware that interconnect technical with visuals. An Interactive Projection Mapping Installation was developed in the process, giving audiences the opportunity to interact directly with the installation and view the interacted graphics in real time. Using a combination of technical, hardware, structures and animations, this installation hopes to give its audience a novel experience while considering the background functionalities that made this installation work.